2018
DOI: 10.1039/c8ra05649h
|View full text |Cite
|
Sign up to set email alerts
|

Partial denitrification coupled with immobilization of anammox in a continuous upflow reactor

Abstract: Based a continuous upflow reactor stably operating, immobilized anammox coupling with partial denitrification (DEAMOX), was successfully achieved after 94 days operation with a 63.5% accumulation rate of NO2−–N and a 98.4% removal rate of NO3−–N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…2. NO3to NO2transformation rate (partial-denitrification activity) This result confirming the finding of studies reported the effects of adding polycaprolactone (PCL), as a solid carbon source, for the removal of the NO3 --N produced during anammox process [38].…”
Section: Partial-denitrification Activitysupporting
confidence: 88%
“…2. NO3to NO2transformation rate (partial-denitrification activity) This result confirming the finding of studies reported the effects of adding polycaprolactone (PCL), as a solid carbon source, for the removal of the NO3 --N produced during anammox process [38].…”
Section: Partial-denitrification Activitysupporting
confidence: 88%
“…However, Wang et al . [43] demonstrated that the increase in pH value led to the decrease in the accumulation of nitrite. In the present study, the strain ZY04 could be normally grown in the pH range of 6–10.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works [8,25,42] have found that an increasing pH promotes the accumulation of nitrite. However, Wang et al [43] demonstrated that the increase in pH value led to the decrease in the accumulation of nitrite. In the present study, the strain ZY04 could be normally grown in the pH range of 6-10.…”
Section: Effect Of Initial Ph Value On Denitrification Performance and Functional Gene Expressionmentioning
confidence: 99%
“…Moreover, Ca 2+ precipitated on the particles reduced the effective mass transfer of the sludge [14]. These and other studies underline the importance of understanding cell immobilization in anammox processes, including granulation and biofilm, to improve the treatment performance of the reactor without changing the original microbial community structure [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%